2000
DOI: 10.1046/j.1365-2249.2000.01217.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular IL-10 gene transfer regulates the expression of collagen-induced arthritis (CIA) in the knee and ipsilateral paw

Abstract: SUMMARYWe studied the effects of local IL-10 application, introduced by a recombinant human type 5 adenovirus vector, in the mouse knee joint during the early phase of CIA. One intra-articular injection with the IL-10-expressing virus (Ad5E1mIL-10) caused substantial over-expression of IL-10 in the mouse knee joint, using virus dosages which did not induce distracting inflammation. High expression of IL-10 was noted for a few days, being maximal at day 1. One intra-articular injection of Ad5E1mIL-10 in the kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 44 publications
2
56
0
Order By: Relevance
“…Intraarticular administration of IL-10 did not reduce the severity of arthritis (34), whereas systemic injection with recombinant IL-10 effectively inhibited disease (36). We detected a higher proportion of IL-10-producing T cells in the spleen after tolerogenic DC treatment, suggesting a systemic increase in IL-10.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Intraarticular administration of IL-10 did not reduce the severity of arthritis (34), whereas systemic injection with recombinant IL-10 effectively inhibited disease (36). We detected a higher proportion of IL-10-producing T cells in the spleen after tolerogenic DC treatment, suggesting a systemic increase in IL-10.…”
Section: Discussionmentioning
confidence: 65%
“…Although it has been shown that treatment with recombinant IL-10 or IL-10-producing T cells is effective for preventing arthritis in mouse models (34,35), contradictory observations have been made regarding the therapeutic effect of IL-10 in established arthritis. Intraarticular administration of IL-10 did not reduce the severity of arthritis (34), whereas systemic injection with recombinant IL-10 effectively inhibited disease (36).…”
Section: Discussionmentioning
confidence: 99%
“…As a control, AdDel70-3 was injected into the left knee joint. We have previously shown that this dose of adenoviral vector does not induce any inflammatory response after IA injection into the mouse knee joint (24). Several days thereafter, mice were killed by cervical dislocation, and the knee joints were harvested for further processing.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, several groups observe high systemic levels of transgene products after local delivery of genes to joints. 8,11,12 However, in our experiments, systemic transgene levels were either below detectable levels or too low to confer a therapeutic effect in our model systems.…”
Section: Introductionmentioning
confidence: 57%